A New Process and Structure for Oxide Semiconductor LCDs. Issue 1 (June 2014) - Yang, Joon‐Young; Lee, Sul; Cho, Seong‐Joon; Jun, Myung‐Chul; Kang, In‐Byeong; Yeo, Sang Deog; Park, Jung‐Ho
Abstract A coplanar TFT structure has excellent characteristics in Δ Vp and channel length compared to conventional etch stopper TFT structure in AOS TFT LCD. In this paper, we introduce new 5 mask coplanar structure which reduces two mask steps compared to conventional 7 mask process. And we fabricated 4.5‐inch HD resolution panel in our R&D line with our new structure, and its transmittance is 12.5% improved by eliminating contact hole pattern.